(untitled) (Bioscience Journal, 2016)
Banana black leaf streak disease caused by the present quarantine pest M. fijiensis occurs in Mato Grosso State since 1999 and requires adoption of sanitation, including detection survey. The aim of this study was to evaluate the distribution of M. fijiensis in Mato Grosso State from 1999 to 2013, as well as how black leaf streak disease periodically was spread in all regions of Mato Grosso State according to the standards of the Ministry of Agriculture, Livestock and Food Supply. Considering the first outbreak year and the previous surveys (Table 1), it can be verified that Mycosphaerella fijiensis Morelet was introduced into Mato Grosso State in accordance with the following periods of times and counties: 2001 to 2003 - Nova Bandeirantes and Paranaíta; 2001 to 2004 - Barra do Bugres and Gaúcha do Norte; 2001 to 2005 - Paranatinga; 2002 to 2004 - Porto Estrela, Santo Afonso, and Tangará da Serra; 2002 to 2005 - Rosário Oeste; 2004 - Acorizal, Guarantã do Norte, and Sinop; 2004 to 2005 - Sapezal; 2005 - Campos de Júlio, Nova Maringá, Poxoréu, and Sorriso; 2005 to 2006 -Marcelândia and Matupá; 2007 - Ãgua Boa, Barra do Garças, Campinápolis, General Carneiro, Novo São Joaquim, and Pedra Preta; 2013 - Canabrava do Norte, Confresa, Porto Alegre do Norte, and São José do Xingu. The dispersal of M. fijiensis throughout both time and space showed to be random in Mato Grosso State and its counties, except among some counties adjacent each other, which can be explained by the movement of infected banana seedlings.